IDENTIFICATION AND IN SILICO CHARACTERIZATION OF TaGSTU30 AND TaTPS1 GENES IN BREAD WHEAT - AMARDEEP* and T. SINGH (The Journal of Research ANGRAU, 2023)
In case of rice, OsGSTU30 and OsTPS1 genes play a critical role in development, metabolism,and abiotic stress responses.In the study, it was aimed to identify and characterizeOsGSTU30 andOsTPS1genes in wheat reference genomic data. Functional domains, physicochemical propertiesand subcellular localization of both genes were identified. The homology modeling method was usedto predict the 3D structures and Ramachandran plots were also predicted to evaluate protein structures.In silico expression profiles of wheat,TaGSTU30 and TPS1 genes at different development tissueswere also identified. Most members of TaGSTU30 and TaTPS1 genes shared similar patterns ofexon/intron structures, including intron phase, intron number, and exon length. Drought responsiveorthologous genes were also identified in recently released reference genomic data of wheat (availableon Ensembl Plants), which were previously identified in rice and Arabidopsis plants. The results ofthe study would permit a better understanding of the structure and advancement of the genes andthe encoded proteins and also provide information for the exploitation of variability for the engineeringof these genes.